Unmasking deepfakes: a multidisciplinary examination of social impacts and regulatory responses - Alanazi, Sami; Asif, Seemal; Caird-Daley, Antoinette; Moulitsas, Irene (Springer, 2025)
This paper presents a comprehensive analysis of deepfake technology and its multifaceted impacts on society, privacy, trust, and information integrity. Deepfakes, synthetic media generated using AI-powered algorithms, pose significant challenges to individual privacy, societal trust, and the integrity of information. To explore these issues, we employed a mixed-methods approach that included in-depth expert interviews with professionals from diverse fields such as law, ethics, artificial intelligence, cybersecurity, and social sciences, along with a dichotomous question survey, which provided comprehensive insights from multiple perspectives. This methodological approach facilitated a multidimensional perspective on the potential risks and benefits of deepfakes. Our findings reveal unanimous concern among experts regarding the profound societal implications of deepfakes, particularly their capacity to amplify disinformation, erode public trust, and inflict psychological harm on individuals. Key themes identified include the urgent need for robust regulatory frameworks, the critical role of media literacy in enhancing public resilience, and the varying impacts of deepfakes across different demographic groups. The consensus among experts points out the necessity for an ethically guided approach to the development and deployment of deepfake technology, emphasizing the importance of interdisciplinary collaboration in crafting effective policy responses. This study advances the ongoing discourse on deepfake technology by providing stakeholders and policymakers with evidence-based recommendations aimed at mitigating the associated risks and harnessing potential benefits. These recommendations promote a balanced and informed approach to navigating the complexities of this emerging technological challenge.
Keywords: 46 Information and Computing Sciences; 4701 Communication and Media Studies; 47 Language, Communication and Culture; Behavioral and Social Science; 8.3 Policy, ethics, and research governance; 4 Quality Education; Deepfake threads; Social impact; Misinformation; Ethical implication; AI regulations; Media literacy; Policy recommendations